Grazing for pollinators: the effects of grazing management on foraging and nesting pollinator communities and habitat - Greenlee, Emma (My University, 2026)
Native pollinators are a vital but threatened component of natural and agricultural systems worldwide, including grasslands. In the Great Plains, bison and prairie dogs were once among the most abundant mammalian grazers, while cattle grazing is a widespread management practice today. Grazers like cattle, bison, and prairie dogs shape the ecosystems around them through herbivory and behavior. However, their effects on pollinator habitat and pollinator communities in prairies are not well understood. This study investigated the effects of grazers on 1) foraging pollinator habitat, communities, and traits and 2) ground-nesting bee habitat and communities. During summer 2024 and 2025, I quantified plant-pollinator networks and measured ground-nesting bee communities across grazing regimes (bison, cattle, prairie dogs, and ungrazed areas) and intensities at sites spanning tallgrass and shortgrass prairies in the Great Plains (Konza Prairie, KS; American Prairie, Charles M. Russell National Wildlife Refuge, and Fort Belknap, MT). I found that grazers primarily influence pollinators indirectly, through effects on floral resources. In Kansas, floral resource availability was higher in bison- and cattle-grazed areas than ungrazed areas, and in Montana, bison and prairie dogs were associated with increased floral resources. In both regions, plant species richness, but not abundance, was positively associated with pollinator species richness. In addition, bee size (a proxy for dispersal ability) did not vary with grazing regime in either region, but larger bee species tended to interact with fewer plant species than smaller bee species in both regions. I found that nesting bee abundance was highest in bison-grazed sites in Kansas, and trended higher in bison-grazed sites in Montana. Nesting bee abundance was primarily driven by aboveground habitat characteristics, particularly floral richness, across regions. Identifying grazing practices that promote robust pollinator communities is critical for the conservation and management of North America’s grasslands, and for informing restoration decisions.
Keywords: Prairie; Bee; Plant-pollinator; Cattle; Bison; Conservation